2022
DOI: 10.3390/cancers14235867
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-4 as Blood-Based Biomarker Enables Detection of Early Ovarian Cancer Stages

Abstract: Ovarian cancer is the third most common gynecological malignancy and has the highest mortality rate. Owing to unspecific symptoms, ovarian cancer is not detected until an advanced stage in about two-thirds of cases. Therefore, it is crucial to establish reliable biomarkers for the early stages to improve the patients’ prognosis. The aim of this study is to investigate whether the ADAM17 substrates Nectin-4, Heparin-binding EGF-like growth factor (HB-EGF) and Amphiregulin (AREG) could function as potential tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Previous studies have investigated the potential of Nectin-2 and Nectin-4 as biomarkers and treatment targets in various cancer types [10][11][12][13][14][15]. In ovarian cancer, serum Nectin-4 may serve as a potential diagnostic marker that helps discriminate benign gynecological diseases from malignancy in a panel with CA125 [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the potential of Nectin-2 and Nectin-4 as biomarkers and treatment targets in various cancer types [10][11][12][13][14][15]. In ovarian cancer, serum Nectin-4 may serve as a potential diagnostic marker that helps discriminate benign gynecological diseases from malignancy in a panel with CA125 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence of Nectin-2 and Nectin-4 overexpression in solid malignancies, several studies have investigated their potential diagnostic and prognostic roles as serum biomarkers in ovarian [10,11], breast [12], lung [13,14], and colorectal cancers [15]. Our recent study demonstrated that nectins are predominantly expressed in the membrane and/or cytoplasm of UC cells with no or faint expression of Nectin-1, slight expression of Nectin-3, and high expression of Nectin-2 and Nectin-4 [16].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between SETD2 deleterious mutation and TMB has placed it in the spotlight as a promising prognostic biomarker for cancer ICI treatment. 56,202 The cell adhesion protein nectin-4 also emerges as a favorable prognostic blood-based biomarker and is known to be overexpressed in several cancer types, including breast, 203 ovarian, 204 endometrial, 205 urothelial, 206 and certain subtypes of bladder cancer. 207 High levels of nectin-4 expression have been correlated with more aggressive cancer behavior, poor prognosis, and shorter survival rates, making it also an emerging prognostic biomarker.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…There is evidence that serum Nectin-4 levels are associated with the grade and progression of ovarian cancer ( 59 ). Notably, Nectin-4 can be detected in the early stages of ovarian cancer, even when CA-125 levels are not significantly elevated in the serum ( 60 ). Although soluble Nectin-4 has great potential and value in the diagnosis and monitoring of ovarian cancer, it still requires large-scale prospective studies for further validation and standardization.…”
Section: Diagnostic Potential Of Nectin-4mentioning
confidence: 99%